(untitled) - Paul Davies (Reading, Massachusetts, 1995)
This book provides a fast-paced introduction to basic programming concepts then move on to a thorough discussion of advanced programming techniques and C features. It provides numerous examples reflecting a wide variety of applications, together with COMPLETE programs; the annotated program listing explaining each programming concept/technique in use
Keywords: c ( computer program language )